The Nexus between Globalization, Foreign Direct Investment and Economic Growth: Experience from Africa - Logan, Chine Sp; Manasseh, Charles O.; Akamobi, Obiageli G.; Ayanbeshishie, Salome A.; Nkwonta, Nkechi C.; Oguchi, Benjamin C.; Jude, Onyemekihian (International Journal of Economics and Financial Issues, 2025)
This study examines the impact of globalization and foreign direct investment (FDI) on economic growth in Nigeria over the period 1960–2019. Economic growth was measured using real gross domestic product (RGDP), while FDI was proxied alongside control variables including net imports, net exports, and exchange rates. Time-series data were employed, and the model was estimated using the Ordinary Least Squares (OLS) method. The stationarity of the variables was assessed using the Augmented Dickey-Fuller (ADF) and Phillips-Perron (PP) unit root tests. Results from the correlation matrix indicate that trade openness and net exports exert a negative influence on economic growth, whereas FDI, net imports, and exchange rates show a positive impact on RGDP. Residual cointegration tests confirm the existence of a long-run equilibrium relationship among the variables. OLS results further reveal a significant long-run relationship between FDI and RGDP, but no significant relationship between trade openness and economic growth. The residual-based error correction model indicates a rapid adjustment from short-run deviations to long-run equilibrium at a speed of 89%. Granger causality tests show no causal relationship between trade openness and economic growth, while a unidirectional causality runs from FDI to economic growth in Nigeria. Based on these findings, it is recommended that the Nigerian government diversify its international trade and strengthen governance and regulatory quality to promote globalization and attract greater FDI inflows.